ANALISIS PENGARUH CITRA MEREK, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG (BERBASIS ANDROID ) TAHUN 2019 (Studi kasus pada dosen dan mahasiswa pengguna smartphone Samsung Di Universitas Boyolali) - Sakurat, Joko; puji rahayu, listyowati; safitri, unna Ria (Universitas Boyolali, 2020)
This research aims to know the influence of brand image, price, and product quality of samsung smartphone purchases on all student users of samsung mobile phones (android-based) at the University of Boyolali. The technique of collecting data which used of these tests are the questionnaire and the interviews conducted in the months april and stay there until 2019 mt gas bali on june .The technique of the sample collection that is used accidental the sampling method of , all of the data have been analyzed from the analysis the percentage of , it is anticipated that analysis linear regression of multiple , the fit and proper test classical economic assumptions agreed to at , the test and been approved f , a satire or a reflecti efforts whatever survives this test and coefficients of determination. Percent of the population in this research was lecturers and students the user of mobile phone samsung ( the android based ) at the university of boyolali , with samples from 100 respondents in the present study. From hypothesis testing in mind that the goal of brand, price and quality of products simultaneously influential buying decision significantly to Samsung mobile phone (android-based). Partially variable of influential brand image quality significantly to purchase Samsung mobile (android-based). While variable pricing and product quality partially do not affect purchase decisions significantly to Samsung mobile phone (android-based). Keywords: brand image, price, product quality, purchase decision.